Revitalisasi Potensi Perajin Patung Kriya Sanggar Utun Cibeusi Pasca Masa Pandic Covid-19 - Gustiyan Rachmadi; Husen Hendriyana; Khoirul Mutaqin (Universitas Lancang Kuning, 2022)
From 1995 to 2014, Cibeusi Village was well-known among the people of West Java and Indonesia as a producer of souvenir handicraft products. Tourist souvenirs are one of the factors that contribute to the overall success of tourism in Bandung and West Java. The article aims to explain the results of the region’s notable creative and artistic products that support tourism by raising city icons, potential natural resources, and artisan resources from the local environment as a result of Community Service activities. Some of Bandung's icons are used as inspiration for the creation of souvenir products made from wood waste by wood carving craftsmen in Cibeusi Village. This Community Service activity employs the Participation Action Research (PAR) method and the Penta Helix system approach in its implementation. This activity has resulted in the enrichment of knowledge and technical skills, the development of creativity in the form of design, and the motivation and regeneration of craftsmen following the Covid-19 Pandemic period, which has been relatively inactive for two years and has severely paralyzed the production activities of Cibeusi village craftsmen.